Women with premenstrual dysphoric disorder have altered sensitivity to allopregnanolone over the menstrual cycle compared to controls—a pilot study - Timby, Erika; Bäckström, Torbjörn; Nyberg, Sigrid; Stenlund, Hans; Wihlbäck, Anna-Carin N.; Bixo, Marie (Psychopharmacology, 2016)
Rationale In premenstrual dysphoric disorder (PMDD), a condition that afflicts 3–8 % of women in fertile ages, the cyclic recurrence of debilitating mood symptoms is restricted to the luteal phase of the menstrual cycle. The progesterone metabolite allopregnanolone is produced by the corpus luteum, and circulating levels are reflected in the brain. Allopregnanolone is a modulator of the GABA A receptor, enhancing the effect of γ-aminobutyric acid (GABA). Previous studies have demonstrated different sensitivity to other GABA A receptor agonists, i.e., benzodiazepines, alcohol, and pregnanolone, in PMDD patients compared to controls. Objectives This study aimed to investigate the sensitivity to intravenous allopregnanolone over the menstrual cycle in PMDD patients. Methods Allopregnanolone, 0.05 mg/kg, was administered intravenously once in the mid-follicular and once in the luteal phase of the menstrual cycle to 10 PMDD patients and 10 control subjects. The saccadic eye velocity (SEV) was recorded by electrooculography as a measurement of functional GABA A receptor activity, at baseline and repeatedly after the injection. A mixed model was used to analyze data. Results There was a highly significant group × phase interaction in the SEV response to allopregnanolone ( F (1,327.489) = 12.747, p < 0.001). In the PMDD group, the SEV response was decreased in the follicular phase compared to the luteal phase ( F (1,168) = 7.776, p = 0.006), whereas in the control group, the difference was opposite during the menstrual cycle ( F (1,158.45) = 5.70, p = 0.018). Conclusions The effect of exogenous allopregnanolone is associated with menstrual cycle phase in PMDD patients and in controls. The results suggest an altered sensitivity to allopregnanolone in PMDD patients.